Modeling Landscape Use for Ungulates: Forgotten Tenets of Ecology, Management, and Inference - Wisdom, Michael J.; Nielson, Ryan M.; Rowland, Mary M.; Proffitt, Kelly M. (Frontiers in Ecology and Evolution, 2020)
Modeling landscape use (i.e., estimating the probability or relative probability of use, occurrence, or selection in a given area and time) by ungulates is an increasingly common practice in research and management. Models of occupancy, distribution, movement, habitat use, and resource selection are formal approaches by which landscape use has been characterized and results published for a myriad of ungulate species across the world. Application of these models has been aided by a growing volume of data on animal locations and model covariates, and the ease of modeling with automated software and high-capacity computers. Models of landscape use are particularly noteworthy in their potential to estimate use at multiple spatial and temporal scales, to characterize individual and population distributions, and to predict spatiotemporal responses to environmental change. Despite these advantages, consideration of ecological processes can be secondary or forgotten. Models without a strong ecological foundation may perform well in case studies (one time, one place) but fail to advance our understanding of a species’ habitat requirements and response to habitat change across a broad inference space that is both ecologically meaningful and of high utility for management. In response, we identify and describe criteria, synthesized from the ecological literature, of direct relevance to modeling landscape use for advancing the ecological understanding and effective management of ungulates. Criteria include the use of (1) a knowledge coproduction framework for scientist-manager collaborations; (2) an explicit inference space with supporting replication for broad inference; (3) process covariates and their ecological scaling to address habitat requirements; (4) ecologically-plausible sets of competing models in development and selection; (5) model evaluation to address objectives and hypotheses of ecological importance; (6) assessment of relationships with animal and population performance; and (7) reliable interpretations for ecological understanding and management uses. Contemporary modeling of landscape use has been challenged by large, disparate data sources and a growing emphasis on statistical methods. However, advances in knowledge and conservation of ungulates based on tenets of ecology, management, and inference are achievable with careful consideration of these criteria.